Supporting a more socially inclusive society in Bangladesh: seeking lessons from different experiences - Centre for Peace and Justice (CPJ), Brac University (Brac University, 2022)
The COVID-19 economic and social crisis offers opportunities to review fundamental questions about national approaches to pluralism, religion’s role in society, and national goals for peace and social cohesion in Bangladesh. This brief offers examples from different countries that address the challenges of living together in diverse societies through secular and religious education efforts.